Evaluation and stability assessment of road cut slope at Bhalupahad of Syangja District along Siddhartha Highway; Western Nepal - Pudasaini, Kusum; Panthi, Krishna Kanta; Mandal, Abhay Kumar (Journal of Engineering and Sciences, 2023)
A road section at Bhalupahad, Syangja of Siddhartha highway was investigated to characterize the rock mass, identify the potential slope failure modes, and determine the stability condition and the major governing factors. The site comprises steep slopes, faces intense rainfall during monsoon periods and falls in a highly active seismic zone. The attitudes of the hill slope and the major discontinuities were measured at 16 different locations and analyzed using stereographic projection. The data was plotted by using Dips 6.0 software. Plane, wedge, and toppling failure modes are possible in the study area. Besides, the Factor of Safety (FOS) for plane and wedge modes of failure has been calculated using Slide2 software. An end-anchored bolt has been installed to increase the FOS at the unstable slope locations. The FOS has increased to 1.3, 1.23, 1.21, 1.28, and 1.29 after support installation, which was 0.43, 0.71, 0.4, 0.55, and 0.57 before giving support at locations 1, 4, 8, 12 and 14 respectively. Rocks were identified as fair to good quality according to Rock Mass Rating (RMR) and partially stable to stable according to Slope Mass Rating (SMR). The results obtained from RMR and SMR agree well with each other and the real slope conditions. Q-slope suggests a slope angle of 60°-65° with a respective Q-slope value of approximately 1.0. The orientation of discontinuities, steep topography, intense rainfall and human intervention are the main causes of slope failures.